Hypoxia-resistant profile implies vulnerability of cancer stem cells to physiological agents, which suggests new therapeutic targets - Cipolleschi, Maria Grazia (Landes Bioscience, 2014)
We have previously shown that peculiar metabolic features of cell adaptation and survival in hypoxia imply growth restriction points that are typical of embryonic stem cells and disappear with differentiation. Here we provide evidence that such restrictions can be exploited as specific antiblastic targets by physiological factors such as pyruvate, tetrahydrofolate, and glutamine. These metabolites act as powerful cytotoxic agents on cancer stem cells (CSCs) when supplied at doses that perturb the biochemical network, sustaining the resumption of aerobic growth after the hypoxic dormant state. Experiments were performed in vivo and in vitro using CSCs obtained from various anaplastic tumors: human melanoma, leukemia, and rat hepatoma cells. Pretreatment of melanoma CSCs with pyruvate significantly reduces their self-renewal in vitro and tumorigenicity in vivo. The metabolic network underlying the cytotoxic effect of the physiological factors was thoroughly defined, principally using AH130 hepatoma, a tumor spontaneously reprogrammed to the embryonic stem stage. This network, based on a tight integration of aerobic glycolysis, cellular redox state, and folate metabolism, is centered on the cellular NADP/NADPH ratio that controls the redox pathway of folate utilization in purine synthesis. On the whole, this study indicates that pyruvate, FH(4), and glutamine display anticancer activity, because CSCs are committed to survive and maintain their stemness in hypoxia. When CSC need to differentiate and proliferate, they shift from anaerobic to aerobic status, and the few mitochondria available makes them susceptible to the injury of the above physiological factors. This vulnerability might be exploited for novel therapeutic treatments.